The Federal Democratic Republic of Ethiopia : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper examines the causes of recent inflation in Ethiopia and discusses possible policy responses. Inflation in Ethiopia has reached a historical peak. Following a drought-related surge of food prices in 2003, it receded to single digits but soon turned back up in 2004 and gradually increased. The paper provides an overview of recent inflation developments, and explores the factors contributing to recent inflation, based on fresh studies and the review of current monetary and external developments. The paper also lays out cross-country analysis with countries experiencing high inflation.